Site-Specific Labeling of the Type 1 Ryanodine Receptor Using Biarsenical Fluorophores Targeted to Engineered Tetracysteine Motifs - Fessenden, James D. (Public Library of Science, 2013)
The type 1 ryanodine receptor (RyR1) is an intracellular Ca(2+) release channel that mediates skeletal muscle excitation contraction coupling. While the overall shape of RyR1 has been elucidated using cryo electron microscopic reconstructions, fine structural details remain elusive. To better understand the structure of RyR1, we have previously used a cell-based fluorescence resonance energy transfer (FRET) method using a fused green fluorescent protein (GFP) donor and a fluorescent acceptor, Cy3NTA that binds specifically to short poly-histidine ‘tags’ engineered into RyR1. However, the need to permeabilize cells to allow Cy3NTA entry as well as the noncovalent binding of Cy3NTA to the His tag limits future applications of this technique for studying conformational changes of the RyR. To overcome these problems, we used a dodecapeptide sequence containing a tetracysteine (Tc) motif to target the biarsenical fluorophores, FlAsH and ReAsH to RyR1. These compounds freely cross intact cell membranes where they then bind covalently to the tetracysteine motif. First, we used this system to conduct FRET measurements in intact cells by fusing a yellow fluorescent protein (YFP) FRET donor to the N-terminus of RyR1 and then targeting the FRET acceptor, ReAsH to an adjacent Tc tag. Moderate energy transfer (∼33%) was observed whereas ReAsH incubation of a YFPRyR1 fusion protein lacking the Tc tag resulted in no detectable FRET. We also developed a FRET-based system that did not require RyR fluorescent protein fusions by labeling N-terminal Tc-tagged RyR1 with FlAsH, a FRET donor and then targeting the FRET acceptor Cy3NTA to an adjacent decahistidine (His(10)) tag. A high degree of energy transfer (∼66%) indicated proper binding of both compounds to these unique recognition sequences in RyR1. Thus, these two systems should provide unprecedented flexibility in future FRET-based structural determinations of RyR1.